PHYSICAL CAPITAL (VACA) DAN KEPUTUSAN PENDANAAN (DEBT TO TOTAL ASSET) TERHADAP KINERJA KEUANGAN (ROA) MELALUI RISIKO KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI 2010-2012 - Savitri, Enni (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
This study aimed to measure the effect of Physical Capital (VACA) and Decision Funding (Debt to Total Assets) toward Financial Performance (ROA) through Financial Risk. This study examined 26 corporate issuers for 3 years ie 2010-2012. The empirical results of this study indicate that the variable Physical Capital has a significant negative effect on financial risk; Funding decisions have a significant positive effect on financial risk; Physical Capital has a significant positive effect on financial performance. Funding and Financial Risk decisions have a significant negative effect on financial performance; Physical Capital mediated by Financial Risk and significant positive effect on financial performance. Funding decisions are not mediated by the Financial Risk and significant negative effect on financial performance. Keywords: Physical Capital, Financing Decisions, Financial Risk, Financial Performance